Globalization for development trade, finance, aid, migration and policy - Goldin, Ian. (New York World Bank, 2007)
Globalization and its relation to poverty reduction and development is not well understood. The revised and updated edition of Globalization for Development identifies the ways in which globalization can overcome poverty or make it worse. The book defines the big historical trends, identifies main global flowstrade, finance, aid, migration, and ideasand examines how each can contribute to undermin
Includes index
Keywords: Globalization